2016
DOI: 10.3389/fvets.2016.00008
|View full text |Cite
|
Sign up to set email alerts
|

Does Early Environmental Complexity Influence Tyrosine Hydroxylase in the Chicken Hippocampus and “Prefrontal” Caudolateral Nidopallium?

Abstract: In adult chickens, the housing system influences hippocampal morphology and neurochemistry. However, no work has been done investigating the effects of the early life environment on chicken brain development. In the present study, we reared 67 commercial laying hens (Gallus gallus domesticus) in two environments that differed in the degree of complexity (aviary or cage system). These two groups were further divided into two age groups. At 20 weeks of age, 18 aviary-reared birds and 15 cage-reared birds were hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…It is possible that the structural enrichments during rearing resulted in neurological changes such as greater hemispheric flexibility that improved adaptive responses to their environments (43). Previous comparisons between cage-reared and aviary-reared hens showed functional lateralization in the hippocampus and caudolateral nidopallium but no differences between the rearing treatments, although all birds were in similar environments for the first 4 weeks of rearing (44). Campbell et al (45) found no differences in the telencephalon or hippocampal volume between enriched-reared and nonenriched-reared hens.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the structural enrichments during rearing resulted in neurological changes such as greater hemispheric flexibility that improved adaptive responses to their environments (43). Previous comparisons between cage-reared and aviary-reared hens showed functional lateralization in the hippocampus and caudolateral nidopallium but no differences between the rearing treatments, although all birds were in similar environments for the first 4 weeks of rearing (44). Campbell et al (45) found no differences in the telencephalon or hippocampal volume between enriched-reared and nonenriched-reared hens.…”
Section: Discussionmentioning
confidence: 99%
“…Adult laying hens (48 weeks of age) kept in different housing systems (battery cages, floor litter pens, and free-range) from 16 weeks onwards showed neuroanatomical differences, with free-range hens having larger cells in the dorsomedial hippocampus than caged but not floor-litter housed hens [ 11 ]. In contrast, neuroanatomical studies on a separate group of birds from the same adult environments showed no rearing-treatment impacts on the immunohistochemical detection of tyrosine hydroxylase in the hippocampus at 20 or 24 weeks of age [ 12 ]. Differences may have been detected in the current study if other measures were made such as dendritic length [ 34 ], neurogenesis [ 35 ], lateralisation, or immunohistochemical staining [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, neuroanatomical studies on a separate group of birds from the same adult environments showed no rearing-treatment impacts on the immunohistochemical detection of tyrosine hydroxylase in the hippocampus at 20 or 24 weeks of age [ 12 ]. Differences may have been detected in the current study if other measures were made such as dendritic length [ 34 ], neurogenesis [ 35 ], lateralisation, or immunohistochemical staining [ 12 ]. Alternatively, the enriched rearing treatment may not have been sufficient to have neurological impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is influence of the local climate the animals also generate heat. According to Cecchin (2016), the metabolism of growing chicken directly influences the temperature of the environment, supported by studies confirming the effect of chick age on avian temperature (FREITAS et al, 2017;TAHAMTANI et al, 2016). Nevertheless, for Freitas (2017), the greatest influence is on environmental factors, as evidenced by Mohammadalipour et al (2017) and Santos et al (2016).…”
Section: Resultsmentioning
confidence: 98%